The synergistic effects of zeolite and urea fertilizer on improved nitrogen use efficiency in oil palm seedling growth - Kautsar, Valensi; Mawandha, Hangger Gahara (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Nitrogen is an essential nutrient for all plants, including oil palm, and the availability of inorganic nitrogen is crucial for supporting the development of oil palm from the seedling stage. However, the fast-release characteristic of urea often leads to its loss before it can be absorbed by plants, resulting in low fertilizer efficiency. To address this issue, one approach is to combine urea with zeolite, a natural mineral with nutrient retention properties. The purpose of this study was to determine the effectiveness of mixing urea with zeolite in oil palm seedlings. During a three-month fertilization application in the oil palm main nursery, conventional fertilization with urea was compared with urea mixed with zeolite, both inactivated and activated, at two percentages: 20% and 40%. The addition of zeolite at various percentages and various zeolite activities produced growth similar to that of urea fertilizer without zeolite. This shows that both activated and non-activated zeolites can be utilized to reduce the amount of urea dosage used in the nursery. The adoption of zeolite at various percentages and levels of activity has the potential to improve nitrogen use efficiency (NUE) in comparison to urea. The application of zeolite led to a significant increase in nitrogen use efficiency (NUE) values. Specifically, the addition of 40% zeolite resulted in considerable NUE values of 18.76% and 22.17% for inactivated and activated zeolite, respectively. In addition to its growth-promoting effects, the use of zeolite in combination with urea can also have cost-saving benefits. The addition of 20% and 40% inactivated zeolite could reduce the cost of nitrogen fertilizer by 27.4% and 36.6%, respectively, compared to 100% urea, making it a more economical option for oil palm plantations. Furthermore, the overall cost of NPK fertilization for three months with inactivated zeolite saved 7.54%-10.09%, while activated zeolite was 5.38%–5.77%.